Developing Speaking Module For Informatics Engineering Students of STTIKOM Insan Unggul Cilegon - Bela Yusti Annasya; Nurhaedah Gailea; Murti Ayu Wijayanti (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
This research and development (R & D) aimed to develop a speaking module for Informatics Engineering students. The sample of this research was taken from semester one of Informatics Engineering at STTIKOM Insan Unggul Cilegon. The researcher used the 9 steps of research and development from Borg & Gall (2003). The researcher found that the students need a module that can support the learning of speaking and enrich speaking skills, as 34% of students preferred a module as a learning medium based on their needs analysis result. The second finding is that the development of the speaking module went well. Based on the 9 steps of R & D, the researcher got some revision and validation from the material expert, the media expert, and the 30 students of Informatics Engineering. The third finding is that the quality of the speaking module is "Excellent" in design criteria, with a 100% validation score based on media expert validation. This means that the module can be used without revision. In addition, it got "Good" criteria in material or the content of the module with an 80% validation score based on material expert validation. This means the module can be used with a little bit of revision. Furthermore, based on students' assessment toward the module, it got "Excellent" criteria with a 100% score from 30 students of Informatics Engineering. Based on the results, it showed that the Speaking Module for Informatics Engineering at STTIKOM Insan Unggul Cilegon can be used as an aid for teaching speaking.